An empirical derivation of the X-ray optic transmission profile used in calibrating the Planetary Instrument for X-ray Lithochemistry (PIXL) for Mars 2020. Issue 2 (24th May 2018) - Heirwegh, C. M.; Elam, W. T.; Flannery, D. T.; Allwood, A. C.
Abstract : Calibration of the prototype Planetary Instrument for X-ray Lithochemistry (PIXL) selected for Mars 2020 has commenced with an empirical derivation of the X-ray optic transmission profile. Through a straightforward method of dividing a measured "blank" spectrum over one calculated assuming no optic influence, a rudimentary profile was formed. A simple boxcar-smoothing algorithm was implemented to approximate the complete profile that was incorporated into PIQUANT. Use of this form of smoothing differs from the more conventional approach of using a parameter-based function to complete the profile. Comparison of element-specific correction factors, taken from a measurement of NIST SRM 610, was used to assess the accuracy of the new profile. Improvement in the low- to mid-energy portion of the data was apparent though the high-energy region diverged from unity, and thus, requires further refinement.